Studi Pustaka Tentang Kerentanan Keamanan E-Learning dan Penanganannya - Pramudita, Reza; Fuada, Syifaul; Majid, Nuur Wachid Abdul (STMIK Budi Darma, 2020)
E-learning is an educational media that use ICT in the learning process. Nowadays, most of the higher education (universities) in Indonesia have integrated the learning process with e-learning systems. By using this system, learning can be done outside the classroom, anytime and anywhere. Based on the literature reviews, e-learning has many positive impacts on higher education components and its ecosystems, i.e., students, lecturers, higher education staff, and campus officials. Although it offers many advantages, similar to the information technology in general, e-learning systems are also vulnerable to security issues. Because, several security holes in the system can be penetrated easily by hackers, where the essential data contained in e-learning has high potential to be spoofed even modified by irresponsible parties. The security aspect of the e-learning system must be considered to minimize risks. Thus, the higher education can run their business as well. This paper aims to elaborate on the e-Learning system, opportunities, challenges, and several offered solutions on it. The research method used in this paper is literature studies from the latest references